2004
DOI: 10.1007/bf02828117
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multiple micronutrient deficiencies amongst pregnant women in a rural area of Haryana

Abstract: There was a high prevalence of micronutrient deficiencies amongst the PW of the area, possibly due to the poor dietary intake of food and low frequency of consumption of food groups rich in micronutrients. The concurrent prevalence of two, three, four and five micronutrient deficiencies were common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
87
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 35 publications
15
87
2
2
Order By: Relevance
“…In this study, unlike zinc, no pregnant women were found deficient in serum copper levels. In line with our observation, a very low prevalence (2.7 %) of copper deficiency was reported from pregnant women in India [16] and in China [35].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, unlike zinc, no pregnant women were found deficient in serum copper levels. In line with our observation, a very low prevalence (2.7 %) of copper deficiency was reported from pregnant women in India [16] and in China [35].…”
Section: Discussionsupporting
confidence: 90%
“…Zinc is required for cellular division and differentiation, and is an essential nutrient for normal embryogenesis. Zinc is a cofactor for the synthesis of a number of enzymes, DNA, and RNA [16]. Zinc deficiency has been associated with complications of pregnancy and delivery, as well as with growth retardation and congenital abnormalities in the fetus [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for synergistic effects of these micronutrients on Fe and folic acid supplementation for the treatment of anaemia is inconsistent (15)(16)(17)(18)(19) , although it is known that Cu has a role in haematopoiesis (20) and vitamin A and b-carotene have been shown to improve Fe absorption, possibly by preventing the inhibitory effects of phytates and polyphenols (21,22) . Regardless of these possible synergies, it is indisputable that girls approaching childbearing age would benefit from the correction of other prevalent nutritional deficiencies, particularly of vitamin A (23)(24)(25)(26)(27) and Ca (28) .…”
Section: Discussionmentioning
confidence: 99%